Celebrating Bowery: Radical costume parties as queer heterotopia in Brisbane. Issue 1 (1st June 2020) - Taylor, Madeline; Hickey, Anna Germaine; Roehrs, Remi
This visual essay explores the creative practice of The Stitchery Collective, which uses costume as a strategy in their participatory works. Inspired by performance artist, queer icon and costume lover Leigh Bowery, The Stitchery Collective has created The Bowery Party, a series of events encouraging radical dress up. These immersive occasions emphasize the significance of costume as enabling joy, community and extravagant social performance. The essay discusses the importance of Bowery as a figure in designing the party in terms of the nature of participant responses, as his legacy provides a subversive approach to costuming the self. The analysis focuses on strategies for and the importance of making and holding space, both physical and virtual, for alternate visions of the body – an empowering ethic that celebrates diversity and inclusivity. The costumes created by the attending public are challenging, often both to wear and to social, gender and body norms. This essay offers a brief example of the costumes created by participants in direct response to Bowery as a radical, slippery and chaotic aesthetic target.